2021
DOI: 10.1007/s00404-021-06215-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of preoperative serum high-density lipoprotein cholesterol and low-density lipoprotein cholesterol levels with the prognosis of ovarian cancer

Abstract: BackgroundThe effect of serum lipids on ovarian cancer is controversial. We conduct this study to evaluate the prognostic value of preoperative plasma lipid pro le in patients with ovarian cancer. MethodsThe medical records of 156 epithelial ovarian cancer patients who underwent surgical resection in our department were retrospectively reviewed and analyzed. Serum lipids pro les, including total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
2
9
1
Order By: Relevance
“…Altered lipid metabolism has emerged as another important feature of OC. Recent studies show that circulating lipid profile may be associated with the risk in OC [ 19 , 20 , 21 , 22 ]. Therefore, not only EVs, but also lipoproteins may be of interest in the OC prognosis and monitoring of the disease [ 8 , 11 , 12 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered lipid metabolism has emerged as another important feature of OC. Recent studies show that circulating lipid profile may be associated with the risk in OC [ 19 , 20 , 21 , 22 ]. Therefore, not only EVs, but also lipoproteins may be of interest in the OC prognosis and monitoring of the disease [ 8 , 11 , 12 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that circulating lipid profile may be associated with the risk in OC [ 19 , 20 , 21 , 22 ]. Therefore, not only EVs, but also lipoproteins may be of interest in the OC prognosis and monitoring of the disease [ 8 , 11 , 12 , 19 , 20 , 21 , 22 ]. EVs (sizes from 30 to ~1000 nm [ 23 ], which includes exosomes with sizes ~30–120 nm [ 11 , 24 ]), lipoproteins (sizes ~7–600 nm [ 25 ]), large protein complexes, and other particles in the overlapping size range, can be present in complex biological samples in different proportions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Lv et al [ 30 ] revealed that the decrease in HDL-C level could indicate liver dysfunction caused by adjuvant chemotherapy in NSCLC, which partly supported the predictive significance of TG/HDL-C for patient prognosis. Additionally, prior research had also shown that lipid imbalances, including elevated TG levels or decreased HDL-C levels, enabled to predict a poorer prognosis in ovarian, colorectal, and breast cancer [ 17 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDL-C can remove cholesterol from peripheral tissues and reverse-transport it to the liver, and thus can be regarded as a potent antioxidant and anti-inflammatory factor [ 16 ]. The metabolism of serum lipids and lipoproteins, such as TG and HDL-C, has a strong correlation to the nutritional status of patients (BMI), diet, and stressful metabolic states [ 17 ]. Reportedly, abnormalities in serum lipids and lipoproteins are strongly bound up with the development as well as the progression of cancer, suggesting that their potential roles in carcinogenesis and providing an innovative theoretical basis for anticancer treatment [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation